The Loyal Republic : Traitors, Slaves, and the Remaking of Citizenship in Civil War America - Mathisen, Erik (Book collections on Project MUSE., 2018)
Mathisen tells the story of how Americans attempted to define what it meant to be a citizen of the United States, at a moment of fracture in the republic's history. As the author demonstrates, prior to the Civil War, American national citizenship amounted to little more than a vague bundle of rights. But during the conflict, citizenship was transformed.